Примирення сторін в адміністративному судочинстві в умовах євроінтеграції України - Сливка, В. В. (ДВНЗ "Ужгородський національний університет", 2021)
Дисертація присвячена формулюванню теоретико-методологічних засад примирення сторін в адміністративному судочинстві та наданню пропозицій щодо вдосконалення адміністративного законодавства України в цій сфері в умовах євроінтеграції. В роботі визначено поняття та особливі ознаки примирення сторін в адміністративному судочинстві. Встановлено мету, завдання, функції, принципи досліджуваного примирення. Визначено суб’єктний склад процедури примирення, встановлено умови та підстави, порядок примирення сторін в адміністративному судочинстві. Враховано досвід окремих держав-членів ЄС (Іспанія, Нідерланди, Німеччина, Франція), а також положення ряду актів ЄС. Узагальнено основні актуальні проблеми в досліджуваній сферіта сформульовано комплекс конкретних пропозицій щодо вдосконалення адміністративно-правового регулювання примирення сторін в адміністративному судочинстві в умовах євроінтеграції України, враховуючи відсутність в ЄС універсальної моделі примирення сторін публічно-правового спору та фрагментарність регулювання примирення сторін в державах-членах ЄС. The dissertation is devoted to the formulation of theoretical and methodological principles of reconciliation of the parties in administrative proceedings and to provide proposals for improving the administrative legislation of Ukraine in this area in the context of European integration. The paper defines the concept and special features of conciliation of the parties in administrative proceedings. It is established that the purpose of conciliation of the parties, as a process, is manifested in the gradual achievement by the parties of a public law dispute of a real consensus on dispute resolution, and, as a result, in the effective resolution of substantive dispute by conciliation. In this sense, conciliation of the parties performs a set of tasks (creating conditions for dialogue between the parties to the dispute; formation in the negotiations of the parties a specific model of mutual concessions that they realize, want to perform such , stimulating, analytical, information and communication, control and supervision, educational and preventive). The system of principles of conciliation of the parties in administrative proceedings are: 1) common law principles; 2) special principles of resolving the case by conciliation (for example, transparency and informativeness of resolving the case by conciliation; dispositiveness, constructive adversarial nature of the parties to the dispute; mandatory entry into force of conciliation conditions after their approval by the court; reasonable terms of resolving the case, etc.); 3) special principles concerning: a) quality, features of dispute resolution through conciliation; principles of accessibility and efficiency; b) voluntary participation in dispute resolution; good faith of all participants in the dispute resolution procedure); characteristics of the qualities of the conciliator (in particular, the principles of competence; independence, impartiality of the conciliator; compliance with the requirements of confidentiality). It is established that the subjective composition of conciliation of the parties is manifested in three models: "simple" (parties to the dispute; the judge who supervises the conciliation, approves the terms of conciliation); "Relatively complicated" (parties to the dispute; a judge who persuades the parties to conciliation and / or fully performs the role of conciliator); 3) "complicated" (parties to the dispute; judge; conciliator). In modern Ukraine there is a "simple" model of the subjective composition of the reconciliation of the parties, which: is characterized by certain features of the "relatively complicated" model; but at the same time it has the potential to transform into a "complicated" model of the subjective composition of the parties. A set of grounds and conditions for resolving a dispute by conciliation in administrative proceedings has been determined. The system of such conditions consists of: 1) positive conditions (the existence of a public law dispute and filing a lawsuit to resolve it; the integrity of the voluntary intentions of the parties to the attempt to reconcile, the implementation of a specific model of conciliation during negotiations and at the time of conciliation; ; reality and rationality of the agreed conditions of conciliation; the presence of the subjects who apply for reconciliation, the appropriate degree of legal personality); 2) negative conditions (inconsistency with the tasks of administrative proceedings in the form of violation of the interests of third parties; the law). The system of grounds covers: normative (norms of the legislation on conciliation of the parties and on the status of the subjects who are parties to the dispute), factual (implementation by the parties of the public-legal dispute of actions on acquisition and realization of the right to conciliation) and procedural-procedural conciliation, court rulings that determine the emergence and exercise of the right to reconciliation). The stages of implementation of the conciliation procedure of the parties in administrative proceedings are: 1) informal and formal initiation and commencement of the conciliation procedure; 2) negotiations in which the parties make a joint statement of conciliation of the parties; 3) submission for approval and approval of the application for conciliation of the parties, in which the court: explains to the parties the consequences of the court decision in connection with the conciliation of the parties; checks the existence of all conditions and grounds for resolving the dispute by, approves the terms of conciliation closes the proceedings or refuses to approve the terms of conciliation and continues the trial. The main current problems in the research area are summarized and a set of specific proposals for improving the administrative and legal regulation of conciliation of the parties in administrative proceeding.
Keywords: судове примирення; адміністративне судочинство; сторони публічно-правового спору; досвід держав-членів ЄС; пропозиції; судово-правова реформа; judicial conciliation; administrative proceedings; parties to a public law dispute; experience of EU member states; proposals; judicial and legal reform